Mentalizing in the presence of another: measuring reflective functioning and attachment in the therapy process$dempirical paper - Talia, Alessandro; Schröder-Pfeifer, Paul; Taubner, Svenja (Psychotherapy research, 2019)
Objective: In this paper, we test the reliability and validity of two novel ways of assessing mentalizing in the therapy context: the Reflective Functioning scale (RF) applied to code psychotherapy transcripts (In-session RF), and the Exploring scale of the Patient Attachment Coding System (PACS), which measures in-session autonomy and is linked with secure attachment in psychotherapy. Method: Before treatment, 160 patients in different types of psychotherapy and from three different countries were administered the Adult Attachment Interview (AAI), which was rated with the RF scale. One early psychotherapy session for each patient was independently rated with the In-session RF scale and with the PACS Exploring scale. Results: Both scales were found to be reliable and to have concurrent validity with the RF scale rated on the AAI, with the PACS Exploring scale found to be a better predictor of RF on the AAI. Conclusions: These results suggest that the PACS Exploring scale might be a practical method for assessing RF in psychotherapy research and a way for researchers and clinicians to track patients’ RF on an ongoing basis. These results also provide information regarding the ways in which differences in RF manifest during psychotherapy sessions.Clinical or methodological significance of this articleResearchers and clinicians can assess patients’ mentalizing based on any single psychotherapy transcript, in many therapeutic modalitiesThe Exploring scale of the Patient Attachment Coding System can yield a reliable measure of reflective functioning based on any single psychotherapy transcript, in many therapeutic modalitiesClient differences in mentalizing manifest in part independently of the therapist’s contributions